In situ Raman investigation of a LiB3O5 melt toward understanding the structural memory phenomena. Issue 48 (18th November 2015) - Feng, Dexuan; Zheng, Guimei; Zhao, Ying; Zhang, Bo; Wan, Songming; You, Jinglin; Hu, Zhanggui
Abstract : After melting, the LiB3 O5 crystal structure collapses to B4 O5 Ø4 groups and B2 O3 molecules, which then polymerize to B3 O4 Ø2 chains. Abstract : Lithium triborate (LiB3 O5, LBO) is the most widely used nonlinear optical crystal. During the LBO crystal melting process, several interesting and important phenomena, called as structural memory, have been found. However, the essence of these phenomena remains unclear. In order to explain these phenomena, high-temperature Raman spectroscopy was used to investigate in situ the structures of a LiB3 O5 melt at different temperatures. Two important structural transformations were found during the LBO crystal melting process: (1) when the crystal begins to melt, every two adjacent basic building units (B3 O4 Ø2 ) in the crystal structure transforms to a B4 O5 Ø4 group and a B2 O3 molecule. (2) Above 860 °C, the B4 O5 Ø4 units react with the B2 O3 molecules to form boron–oxygen chains whose minimal repeated unit is the B3 O4 Ø2 six-membered ring. These results prove that LBO is an incongruently melting compound and provide a rationale for understanding the special structural memory phenomena.